The Badi: Changing Social Norms and Empowerment - Katuwal, Chandra Bahadur (Patan Pragya, 2022)
This article is based on the study conducted in Narayan municipality of Dailekh district. Main argument of the article is socially constructed and changing in social norms makes change in relationship. It is perceived that Badi community represents woman -friendly community. They wish to have a daughter rather than son. However, now Badi community has changed its norms. Now, Badi community prefer son to a daughter. In the past, Badi women used to dance, sing and run their family. However, now, due to availability of different types of musical system and instruments, Badi women’s profession has replaced by modern entertainment system. With their profession lost, Badi male took lead of the family care. One of the oldest respondents of Badi community has mentioned "pahile hami khanekura jamma garna gauma jantheu hamra baddamantha hamro bato kurera basthe, aajkal ulto vako xa hami bato herxau" (in the past women used to go village to collect foods and their husbands were waiting respectfully to them but now just opposite, men are breadwinner and women are dependent on men). It has been taken that the Badi community as their namesake Badhyabdak (playing a musical instrument) as entertainer, storyteller and singer but due to easily available music system and other instruments of entertain their professions became in danger. Badi community changed their occupation as a worker, daily wage labor, driver and other. Thus, slowly Badi women are subjugated, oppressed, dominated and disempowered.